Landscape Political Economy Media in Kompas Gramedia Group (KGG): A Chomsky’s Media Propaganda Analysis - Nur Allan Lasido (Potret Pemikiran, 2023)
Kompas Gramedia Group (KGG) is one of Indonesia's largest corporations with a network of media businesses. This study aims to analyze and map two aspects: How the mapping of business networks and the development of KGG media concentration in several regions in Indonesia, as well as political and economic factors that influence the formation (construction) of strengthening the KGG conglomerate as one of the largest media companies in Indonesia today. This study uses qualitative research methods through the instrument of political economy analysis of media propaganda models against five filters/layers of political media economy developed by Noam Chomsky. The study results found that KGG built a media business arena almost evenly throughout Indonesia. Arena contestation has become a bone of contention because it has significant economic opportunities to create new expansion areas. For example, areas outside Jakarta as information control mechanisms from Jakarta can control suburbs as the center of information. In addition to the work of five media layers on Kompas, it can move quickly to reach one point, namely the element of diversity or diversity of media content consumed by the audience to be nonexistent. This condition needs to be watched out as a threat to the independence of the fulfillment of citizens' rights to diverse information, but the content is not uniform.